PENGARUH CUSTOMER EXPERIENCE, CUSTOMER SATISFACTION, DAN WORD OF MOUTH TERHADAP CUSTOMER LOYALTY PADA APLIKASI TIKET BIOSKOP - Lie, Yenita Flowrenza; Panjaitan, Arop Ria Saulina (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
Mobile applications are the right platform in combining elements of customer experience and customer satisfaction to build customer loyalty, it can be seen that currently many companies are turning to the digital world by developing mobile applications as a forum for interaction with customers. The aim of this research is to find out the impact of customer experience, customer satisfaction and word of mouth on customer loyalty in purchasing movie tickets through the TIX ID application. The research approach used in this study is quantitative and analyzed using multiple linear regression. Sampling using non-probability sampling techniques involving 140 respondents who use the TIX ID application in Jabodetabek. The results show that partially customer experience, customer satisfaction, and word of mouth have a positive effect on customer loyalty, and simultaneously have a positive effect on customer loyalty. The managerial implication of this research is that management needs to ensure that complaint services related to ticket purchase errors in the TIX ID application are improved, by analyzing common errors. Companies can also take advantage of the power of word of mouth by providing a satisfying experience to customers. Because a good customer experience will tend to have a higher level of customer loyalty.